A single cytosine deletion in the OsPLS1 gene encoding vacuolar-type H+-ATPase subunit A1 leads to premature leaf senescence and seed dormancy in rice - Yang, Xi (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology.